Nazruler Lokosurer Gaan : Ekti Porjalochona (Jagannath University Journal of Arts, 2026)
Bengal's folk music is a tapestry of rich diversity, with each region contributing unique melodies and lyrics. The origins of these folk songs trace back to the 10th to 12th centuries, notably with the creation of the Charyapads. Over time, these songs evolved into various forms, including Vaishnava Padabali and Shakta compositions reflecting the regions spiritual and cultural milieu. The spectrum of Bengali folk music encompasses genres such as Kirtan, Baaul, Bhatiali, Bhawaiya, Jari, Sari, Kobi Gaan, Murshidi, Marfati, Leto, Gambhira, Jhumur, and Aalkap etc. Each genre offers a distinct narrative and musical style, capturing the essence of the Bengal's cultural heritage. Kazi Nazrul Islam made significant contributions to Bengali music by composing songs across nearly all these folk genres. Born in 1899 in Churulia, Bengal, Nazrul's upbringing amidst a rich tapestry of folk traditions deeply influenced his musical compositions. His proximity to regions where Santals and traditional Jhumur songs were prevalent left an indelible mark on his work. Nazrul's innovative approach led to the creation of Nazrul Geeti, a genre that melded revolutionary fervor with spiritual, philosophical, and romantic themes. His songs, numbering nearly 4,000, continue to inspire and influence Bengali music, underscoring his unparalleled role in enriching the region's musical heritage.Jagannath University Journal of Arts, v-15, i-01, 2025:p26-38